2011
DOI: 10.1007/s00395-011-0237-1
|View full text |Cite
|
Sign up to set email alerts
|

The link between metabolic abnormalities and endothelial dysfunction in type 2 diabetes: an update

Abstract: Despite abundant clinical evidence linking metabolic abnormalities to diabetic vasculopathy, the molecular basis of individual susceptibility to diabetic vascular complications is still largely undetermined. Endothelial dysfunction in diabetes-associated vascular complications is considered an early stage of vasculopathy and has attracted considerable research interests. Type 2 diabetes is characterized by metabolic abnormalities, such as hyperglycemia, excess liberation of free fatty acids (FFA), insulin resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 108 publications
(119 reference statements)
4
77
0
2
Order By: Relevance
“…Apoptosis is the ultimate endothelial cell dysfunction and has been shown to predispose the vessel to the development of an atherosclerotic plaque (93). To better understand how nutrient-induced impairment of autophagy might contribute to apoptosis, we characterized an earlier indicator of endo- thelial dysfunction, inflammation, in HAECs exposed to excess nutrients.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis is the ultimate endothelial cell dysfunction and has been shown to predispose the vessel to the development of an atherosclerotic plaque (93). To better understand how nutrient-induced impairment of autophagy might contribute to apoptosis, we characterized an earlier indicator of endo- thelial dysfunction, inflammation, in HAECs exposed to excess nutrients.…”
Section: Resultsmentioning
confidence: 99%
“…Palmitic acid stimulates the production of superoxide radicals through activating NADPH oxidases and downregulation of eNOS [12,13]. Superoxide reacts with NO, forming the potent and versatile oxidant peroxynitrite (ONOO•−) which may oxidize the eNOS cofactor tetrahydrobiopterin or destabilize the eNOS dimer, causing uncoupling of eNOS [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that chronic elevations in plasma free fatty acids (FFAs) contribute to the development of endothelial damage, diminished endothelium-dependent vasodilation, and hypertension [9,10] by triggering overproduction of reactive oxygen species (ROS), leading to uncoupling of eNOS [11]. Palmitic acid, the most prominent FFA in the bloodstream, stimulates the production of ROS, at least in part, through activating nicotinamide adenine dinucleotide phosphate (NADPH) oxidases and down-regulation of eNOS and associated protective pathways, including nuclear factor-erythroid 2-related factor 2 (Nrf2) [12,13]. Decreasing lipotoxicity and its associated oxidative stress, as well as promoting up-regulation of anti-oxidant enzymes and cytoprotective proteins, may be key components to prevent and treat cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance also promotes atherosclerosis by increasing triglycerides, apolipoprotein B, and low-density lipoproteins. In addition, concentrations of very low-density lipoproteins are generated in response to increased synthesis of apolipoprotein B [23] . Coronary events in diabetics result from a prothrombotic state.…”
Section: Diabetes and Cardiac Diseasementioning
confidence: 99%